Insects of forensic significance in Argentina - Oliva, Adriana (2001)
Records from forensic expertises and trappings with beef baits conducted in Buenos Aires, Argentina (34°36′S), show that the dominating species are widespread ones (Calliphora vicina and Phaenicia sericata), with different behaviour in each large latitudinal zone. It is suggested that the range of the yearly photoperiod variation has an influence in the behaviour of the blowflies, making up for differences in the succession patterns. The Calliphorid blowflies Cochliomyia macellaria and Chysomya albiceps were found on indoors corpses; the latter also on outdoors corpses when blood was shed, and in that case as primary. Three species of beetles of the genus Dermestes, which had been associated with mummified remains, appeared 10-30 days after death. The Silphid beetle Hyponecrodes sp. cf. erythrura was found on outdoor copses in rural environments. The Nitidulid beetle Carpophilus hemipterus was found in association with the cheese skipper Piophila sp. (Diptera: Piophilidae) in medullar cavities of bones after ca. 30 days; to this association is often added the Clerid Necrobia rufipes. Lepidoptera Tineidae appear on the head of mummified indoors corpses. North of parallel 32°S, the Muscid grave-fly Ophyra sp. was found breeding on a corpse outdoors in summer. A division by latitude and climate is proposed for Argentina, and an extended system is proposed for the world.